COVID-19 interim guidance: return to sports (Americal Academy of Pediatrics, 2020)
Approximately 35 to 45 million youth 6 to 18 years of age participate in some form of athletics. The coronavirus disease 2019 (COVID-19) pandemic has affected many aspects of the lives of children and families, including youth sport activity. As children present for health supervision visits and preparticipation physical evaluations, parents and athletes likely will ask questions about how best to ensure safety when considering a return to sports participation. This guidance is intended for pediatricians to inform families on how to mitigate risk and prevent the spread of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, to others both within sports and within families and the community. Pediatricians should also refer to their state regulations and guidance associated with return to sports as states are allowing practice and competition to resume at different stages.